f-frequently hypercyclic C0-semigroups on complex sectors - Belkacem Chaouchi, Marko Kostic, Stevan Pilipovic, Daniel Velinov (SPRINGER BASEL AG, 2020)
We analyze f -frequently hypercyclic, q-frequently hypercyclic (q > 1), and frequently hypercyclic C0-semigroups (q = 1) defined on complex sectors, with values in separable infinite-dimensional Fréchet spaces. Some structural results are given for a general class of F-frequently hypercyclic C0-semigroups, as well. We investigate generalized frequently hypercyclic translation semigroups and generalized frequently hypercyclic semigroups induced by semiflows on weighted function spaces. Several illustrative examples are presented.
Keywords: C0-Semigroups on complex sectors , F-Frequent hypercyclicity , f -Frequent hypercyclicity, Translation semigroups and semigroups induced by semiflows, Fréchet spaces